Proceedings of the 3rd International Conference of Business, Accounting, and Economics, ICBAE 2022, 10-11 August 2022, Purwoker 2022
DOI: 10.4108/eai.10-8-2022.2320917
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Financial Leverage, ROA, Ownership Concentration, Listing Delay on Levels Underpricing During Initial Public Offering (IPO) in Manufacturing Companies on the Indonesia Stock Exchange (2016-2020 Period)

Abstract: Theipurpose of this study is to analyze the factors that influence the level of underpricing of manufacturing companies that conduct IPO (Initial Public Offering). This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2016-2020. The method used in this research is purposive sampling. With a sample of 45 IPO companies with 5 years of observation. Based on the results of the regression analysis in the study, it shows that the Financial Leverage variable has a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
0
0
Order By: Relevance
“…Then Irawan & Nasution (2023) added that their study concluded that DAR does not affect the level of underpricing. In contrast, the results of a study by Rahmawati et al (2022) Asserts that there is a positive influence of the Debt to Asset Ratio (DAR) on the level of underpricing. Putri & Sari (2023) reported with the results of the DAR variable there is an influence on underpricing based on the results of their study.…”
Section: Theoretical Backgroundmentioning
confidence: 96%
“…Then Irawan & Nasution (2023) added that their study concluded that DAR does not affect the level of underpricing. In contrast, the results of a study by Rahmawati et al (2022) Asserts that there is a positive influence of the Debt to Asset Ratio (DAR) on the level of underpricing. Putri & Sari (2023) reported with the results of the DAR variable there is an influence on underpricing based on the results of their study.…”
Section: Theoretical Backgroundmentioning
confidence: 96%